Determination of Patient Safety Culture of Pediatric Surgery Nurses - Gülçin KORKMAZ YENİCE; Figen Işık ESENAY; Tufan Aslı SEZER (Atatürk University, 2021)
Aim: Pediatric and surgical services are risky units in terms of patient safety errors. This research was carried out to determine the patient safety culture of pediatric surgical nurses and factors affecting. Methods: This descriptive and cross-sectional study was conducted between 20 June 2019 and 20 February 2020 with 54 nurses registered in the Association of Pediatric Surgical Nurses. The data were collected by using the "Introductory Information Form" and "Patient Safety Culture Scale" by using online survey method. Results: The average age of the nurses participating in the research was 32.6±7.35 years, and the duration of work as a pediatric surgery nurse was 8.87±6.89 years. The total score of nurses from the patient safety culture scale was 2.91±0.28, the lowest score was found in the "Unexpected Incident and Error Reporting" sub-dimension (2.83±0.35), and the highest score in the "Employee Behavior" sub-dimension (2.98 ± 0.29). The patient safety culture levels of nurses were affected by the institution worked, education level, patient safety education and report a problem before, education level, patient safety training before and report a problem before. Conclusions: Pediatric surgery nurses participating in the study were found to have a positive patient safety culture. Nurses' unexpected incident and error reporting levels are low and should be supported.